High-adhesion anti-wear composite modified flat plate denitration catalyst and preparation method thereof
Patent Information
- Application Number
- CN202611129433.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]目前,平板式催化剂在实际应用中存在诸多技术缺陷,如下:其一,催化剂泥料与不锈钢筛网板之间的黏附力不足,在烟气冲刷、温度波动等工况下,易发生催化剂层脱落现象;其二,催化剂整体机械强度和耐磨性欠佳,长期受烟气中飞灰冲刷后,催化剂层磨损加剧,导致活性位点流失,催化效率大幅下降;其三,活性组分分散性较差,易团聚,进一步降低催化反应效率,且高温工况下易发生烧结失活,使用寿命较短;其四,部分催化剂为提升强度过度添加增强组分,导致催化剂阻力增大,不适用于燃机等对低阻力有要求的场景,或黏附力提升的同时牺牲了催化活性
1.黏附力显著提升:本发明采用改性剂处理的累托石,结合硅溶胶粘结助剂,配合中温涂覆工序,使催化剂泥料与不锈钢筛网板之间形成牢固的化学键合,黏附力较现有技术提升30%以上,有效避免催化剂层脱落,同时硅溶胶可提升催化剂的耐磨性能和比表面积,促进活性组分分散,兼顾黏结性能与催化性能;累托石的层状结构可进一步增强与泥料的结合度,黏结稳定性优于传统高岭土。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a high-adhesion, wear-resistant composite modified plate-type denitrification catalyst and its preparation method, belonging to the technical field of plate-type denitrification catalysts. Background Technology
[0002] As a core component of selective catalytic reduction (SCR) flue gas denitrification technology, flat-plate catalysts are made of thin stainless steel screen plates as substrates. They are assembled by coating the substrate surface with active mud and then cutting, pleating, and calcining. They have advantages such as strong resistance to fly ash blockage and poisoning and are widely used in industrial scenarios with unstable coal types and high dust content in flue gas.
[0003] Currently, flat-plate catalysts suffer from several technical drawbacks in practical applications, including: First, insufficient adhesion between the catalyst sludge and the stainless steel screen plate, leading to catalyst layer detachment under conditions such as flue gas scouring and temperature fluctuations. Second, poor overall mechanical strength and wear resistance; prolonged exposure to fly ash in flue gas exacerbates catalyst layer wear, resulting in the loss of active sites and a significant decrease in catalytic efficiency. Third, poor dispersion of active components, leading to agglomeration and further reducing catalytic reaction efficiency; also, sintering deactivation is prone to occur under high-temperature conditions, resulting in a short service life. Fourth, some catalysts excessively incorporate reinforcing components to increase strength, leading to increased catalyst resistance and unsuitability for applications requiring low resistance, such as gas turbines, or sacrificing catalytic activity while increasing adhesion. Therefore, developing a catalyst with high adhesion and good wear resistance is of great significance. Summary of the Invention
[0004] In view of the above-mentioned prior art, the present invention provides a high-adhesion, wear-resistant composite modified flat plate denitrification catalyst and its preparation method.
[0005] This invention is achieved through the following technical solution: A high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst is made from the following components in parts by weight: 50-80 parts titanium dioxide, 3-18 parts modified attapulgite, 3-12 parts composite fiber, 2-15 parts plasticizer, 1.2-4 parts active component, 0.3-1.5 parts dispersant, 1-5 parts binder, 0.2-1.0 parts tungsten-based modifier, 0.1-0.8 parts rare earth dopant, and 10-30 parts water; The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of (2.8-3.2):1, preferably 3:1. The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:(0.8-1.2). The glass fiber is composed of two specifications: specification 1: diameter 1.5-3 μm, length 1-3 mm; specification 2: diameter 1.5-3 μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:1. The carbon fiber is composed of two specifications: specification 1: diameter 1.5-3 μm, length 1-3 mm; specification 2: diameter 1.5-3 μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:1. The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:(1 to 1.5).
[0006] Furthermore, the titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with the weight ratio of anatase titanium dioxide to rutile titanium dioxide being (6-8):(2.5-3.5), preferably 7:3, and the particle size being 50-100 nm.
[0007] Furthermore, the plasticizer is selected from any one or more of polyvinyl alcohol (PVA), polyethylene glycol (PEG), and hydroxypropyl methylcellulose (HPMC).
[0008] Furthermore, the dispersant is selected from sodium citrate and / or polycarboxylate.
[0009] Furthermore, the adhesive is selected from silica sol with a solid content of 30% to 50%.
[0010] Furthermore, the tungsten-based modifier is selected from niobium tungstate and / or zirconium tungstate.
[0011] Furthermore, the rare earth dopant is selected from samarium oxide (Sm2O3) and / or terbium oxide (Tb4O7).
[0012] Preferably, it is made of the following components in parts by weight: 60-75 parts titanium dioxide, 5-15 parts modified palladium, 5-10 parts composite fiber, 5-12 parts plasticizer, 1.5-3 parts active component, 0.5-1.2 parts dispersant, 2-4 parts binder, 0.4-0.8 parts tungsten-based modifier, 0.3-0.6 parts rare earth dopant, and 15-25 parts water.
[0013] The preparation method of the high-adhesion, wear-resistant composite modified flat-plate denitration catalyst includes the following steps: S1: Preparation of modified attapulgite: Take attapulgite, wash it with water, filter it, dry it, and then mix it with a modifier. The weight ratio of attapulgite to modifier is 10:(0.5~1). Treat it with hydrothermal heat at 180~420℃ for 1~3.5 hours, dry it, and grind it to 100~120 mesh to obtain modified attapulgite. The attapulgite is attapulgite ore with a purity >90wt.%. S2: One-time mixing: Add modified attapulgite, plasticizer, dispersant and 50% to 70% titanium dioxide to the mixer and dry mix for 2 to 12 minutes; then add water and carry out one-time mixing at 25 to 65°C for 8 to 25 minutes to obtain the preliminary mixture. S3: Secondary mixing: Add the composite fiber and the remaining titanium dioxide to the initial mixing material, heat to 45-75℃, and carry out secondary mixing for 8-18 minutes to ensure that the fiber is evenly dispersed in the mixing material and avoid agglomeration, thus obtaining the secondary mixing material. S4: Three-stage mixing: The active components, binder, tungsten-based modifier, and rare earth dopants are added to the primary mixture. The temperature is maintained at 45–75℃, and the pH value is adjusted to 8–9 (by adjusting the pH value with lactic acid and ammonia). The mixture is then mixed three times for 5–12 minutes to obtain catalyst slurry. The plasticity of the catalyst slurry is 0.3–0.8, and the moisture content is 22%–32%. S5: Ultrasonic treatment and granulation: The catalyst sludge is placed in a container equipped with ultrasonic transmitters on all sides and ultrasonically treated at a frequency of 20-800 kHz for 3-25 min to break up agglomerates in the sludge and improve the dispersibility of components; then granulation is performed to obtain granular active sludge. S6: Coating and molding: The active mud material is extruded and coated onto a stainless steel screen plate through a coating roller equipped with an electromagnetic rotary heating device. The temperature of the coating roller is controlled at 80-180℃, and the coating thickness is 0.3-0.8 mm. After coating, the coated plate is placed in a drying oven and dried at 120-180℃ for 3-8 minutes to remove surface moisture. S7: Cutting, pleating and calcining: Cut the dried coated plate to the preset size, and then pleat it. The pleating angle is 15° to 40°, the plate width is 12 to 18 mm, and the pitch is 2 to 3 mm. This increases the specific surface area while reducing the flue gas resistance. Combine the pleated plates into catalyst units, put them into a calcining furnace, and heat them to 480 to 620°C at a heating rate of 5 to 10°C / min. Calcinate them at this temperature for 3 to 10 hours. Cool to room temperature to obtain the high-adhesion, wear-resistant composite modified flat plate denitrification catalyst.
[0014] Application of the high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst in selective catalytic reduction flue gas denitrification.
[0015] This invention relates to a high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst, using attapulgite as the raw material. Attachpulgite itself possesses a layered structure and excellent bonding properties. Through grafting treatment with a modifier, its viscosity in the mid-temperature range (100–200°C) is significantly improved, enhancing its adhesion to catalyst sludge and stainless steel screen plates. Simultaneously, it improves the catalyst's temperature resistance and wear resistance, solving the problem of rapid viscosity decay with a single modifier. Its bonding properties are superior to kaolin, and it exhibits stronger resistance to high-temperature sintering. In modifying attapulgite, this invention abandons commonly used C5 / C9 petroleum resin. Instead, it selects a more specific tungsten-based modifier, which synergistically enhances the active component, significantly improving catalytic activity and widening the active temperature range. It also inhibits high-temperature sintering deactivation while avoiding the defects of traditional tungsten-based modifiers, such as easy agglomeration and reduced adhesion. This invention employs rare-earth dopants to optimize the dispersibility of active components, enhance the catalyst's resistance to poisoning, and synergistically strengthen the adhesion stability between the catalyst and the stainless steel screen plate. Furthermore, it achieves lower doping levels and more significant synergistic effects. This invention utilizes composite titanium dioxide, which has a specific surface area more than 20% higher than that of single anatase, providing more active sites while improving the dispersibility of active components and the weather resistance of the catalyst, thus enhancing the long-term stability of catalytic efficiency. Gradient-temperature calcination during preparation prevents catalyst layer cracking, further improving adhesion and mechanical strength, while simultaneously promoting the full dispersion and activation of active components.
[0016] The catalyst of this invention possesses excellent performance: high adhesion, high mechanical strength, good wear resistance, high catalytic efficiency, and low flue gas resistance, making it suitable for applications requiring low resistance and demonstrating strong applicability. Compared with existing technologies, it has the following significant advantages: 1. Significantly Improved Adhesion: This invention uses attapulgite treated with a modifier, combined with a silica sol binder, and a medium-temperature coating process to form a strong chemical bond between the catalyst sludge and the stainless steel screen plate. The adhesion is improved by more than 30% compared with the prior art, effectively preventing the catalyst layer from falling off. At the same time, the silica sol can improve the wear resistance and specific surface area of the catalyst, promote the dispersion of active components, and balance the bonding performance and catalytic performance. The layered structure of attapulgite can further enhance the bonding degree with the sludge, and the bonding stability is better than that of traditional kaolin.
[0017] 2. Synergistic Optimization of Mechanical Strength and Wear Resistance: This invention employs a composite of glass fiber and carbon fiber of different specifications, with the fibers uniformly dispersed in the catalyst slurry to form a three-dimensional network reinforcement structure. This not only improves the overall mechanical strength of the catalyst (increasing flexural strength by more than 25%) but also ensures the toughness of the catalyst, solving the problem of inhibiting flexural performance when improving wear resistance in existing catalysts. At the same time, the synergistic effect of modified attapulgite and binder further enhances the wear resistance of the catalyst, enabling it to withstand long-term erosion by high-dust flue gas and extend its service life to more than 5 years. The high-temperature resistance of modified attapulgite also effectively avoids the degradation of bonding performance under high-temperature conditions.
[0018] 3. High and stable catalytic efficiency: This invention uses tungsten-based modifiers in synergy with the original active components, combined with rare earth dopants and dispersants, effectively solving the problem of active component agglomeration. This ensures that the active components are uniformly dispersed on the surface of the composite titanium dioxide carrier, resulting in high utilization of active sites. At the same time, the selection of composite titanium dioxide provides more loading sites for the active components. Combined with the optimized calcination process, the denitrification efficiency of the catalyst is stabilized at over 95%, and it maintains high activity in a wide temperature range of 280–480℃. This makes it suitable for high-temperature flue gas conditions, while reducing SO2 / SO3 conversion rate, minimizing the risk of secondary pollution, and exhibiting strong resistance to poisoning.
[0019] 4. Low resistance adaptable to multiple scenarios: By optimizing the pleating parameters (wave angle, plate width, pitch), this invention effectively reduces flue gas resistance while increasing the specific surface area of the catalyst, making the catalyst resistance comparable to that of honeycomb or corrugated plate catalysts used in gas turbines. It can be widely used in different denitrification scenarios such as coal-fired power plants and gas turbines, making it more applicable.
[0020] 5. Simple preparation process and strong controllability: The preparation method of the present invention has a clear process flow, the parameters of each process are easy to control, no complex production equipment is required, the production cost is low, and it is suitable for large-scale industrial production; at the same time, through three mixing, ultrasonic treatment and gradient calcination processes, the stability and repeatability of catalyst performance are further improved.
[0021] The various terms and phrases used in this invention have their general meanings known to those skilled in the art. Detailed Implementation
[0022] The present invention will be further described below with reference to embodiments. However, the scope of the present invention is not limited to the following embodiments. Those skilled in the art will understand that various changes and modifications can be made to the present invention without departing from the spirit and scope thereof.
[0023] Unless otherwise specified, the instruments, reagents, and materials used in the following embodiments are all conventional instruments, reagents, and materials already available in the prior art and can be obtained through legitimate commercial channels. Unless otherwise specified, the experimental methods and detection methods used in the following embodiments are all conventional experimental methods and detection methods already available in the prior art.
[0024] Example 1: Preparation of a high-adhesion, wear-resistant composite modified planar denitration catalyst A high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst is made from the following components in parts by weight: 60 parts titanium dioxide, 5 parts modified attapulgite, 5 parts composite fiber, 5 parts plasticizer, 1.5 parts active component, 0.5 parts dispersant, 2 parts binder, 0.4 parts tungsten-based modifier, 0.3 parts rare earth dopant, and 15 parts water.
[0025] The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of 3:1.
[0026] The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:1. The glass fiber is composed of two specifications: specification 1: diameter 2μm, length 1-3 mm; specification 2: diameter 2μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:1. The carbon fiber is composed of two specifications: specification 1: diameter 2μm, length 1-3 mm; specification 2: diameter 2μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:1.
[0027] The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:1.
[0028] The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of 7:3 and a particle size of 80 nm.
[0029] The plasticizer is polyvinyl alcohol.
[0030] The dispersant is sodium citrate.
[0031] The bonding agent is a silica sol with a solid content of 40%.
[0032] The tungsten-based modifier is niobium tungstate.
[0033] The rare earth dopant is samarium oxide (Sm2O3).
[0034] The preparation method of the high-adhesion, wear-resistant composite modified flat-plate denitration catalyst includes the following steps: S1: Preparation of modified attapulgite: Take attapulgite ore with a purity of 92wt.%, wash it with water, filter it, dry it, mix it with a modifier, the weight ratio of attapulgite to modifier is 10:0.6, hydrothermally treat it at 250℃ for 2 hours, dry it, grind it to 110 mesh, and you will get modified attapulgite. S2: One-time mixing: Add modified attapulgite, plasticizer, dispersant and 60% titanium dioxide (36 parts) into the mixer and dry mix for 5 min; then add water and mix once at 40℃ for 15 min to obtain the preliminary mixture. S3: Secondary mixing: Add the composite fiber and the remaining titanium dioxide to the initial mixing material, heat to 60℃, and carry out secondary mixing for 12 minutes to ensure that the fiber is evenly dispersed in the mixing material and avoid agglomeration, thus obtaining the secondary mixing material. S4: Three-stage mixing: Add the active components, binder, tungsten modifier and rare earth dopant to the primary mixture, maintain the temperature at 60℃, adjust the pH value to 8.5 (by adjusting the pH value with lactic acid and ammonia water), and perform three-stage mixing for 8 minutes to obtain catalyst slurry. The plasticity of the catalyst slurry is 0.5 and the moisture content is 28%. S5: Ultrasonic treatment and granulation: The catalyst sludge is placed in a container equipped with ultrasonic transmitters on all sides and ultrasonically treated at a frequency of 400kHz for 15 minutes to break up agglomerates in the sludge and improve component dispersibility; then granulation is performed to obtain granular active sludge. S6: Coating and molding: The active mud material is extruded and coated onto a stainless steel screen plate through a coating roller equipped with an electromagnetic rotary heating device. The temperature of the coating roller is controlled at 120℃ and the coating thickness is 0.5 mm. After coating, the coated plate is placed in a drying oven and dried at 150℃ for 5 min to remove surface moisture. S7: Cutting, pleating and calcining: Cut the dried coated plate to the preset size, and then pleat it. The pleating angle is 25°, the plate width is 15 mm, and the pitch is 2.5 mm. This increases the specific surface area while reducing the flue gas resistance. Combine the pleated plates into catalyst units, put them into a calcining furnace, heat them to 550°C at a heating rate of 8°C / min, and calcine them for 6 hours. Cool them to room temperature to obtain the high-adhesion, wear-resistant composite modified flat plate denitrification catalyst.
[0035] Tests showed that the catalyst had an adhesion strength of 1.8 MPa to the stainless steel screen plate, a bending strength of 12.5 MPa, and a denitrification efficiency of 96.2%. The denitrification efficiency remained stable at over 95% within the temperature range of 280–480℃.
[0036] The catalyst was verified through simulated poisoning experiments and showed excellent anti-poisoning performance: after treatment in an atmosphere containing K2O for 8 hours, the denitrification efficiency remained above 90%; after treatment in an atmosphere containing Na2O for 8 hours, the denitrification efficiency remained above 90%; after treatment in an atmosphere containing As2O3 for 8 hours, the denitrification efficiency remained above 90%.
[0037] The catalyst has a service life of up to 5.5 years: Catalyst samples were placed in a fixed-bed reactor simulating coal-fired flue gas (containing SO2, H2O, etc.) and subjected to accelerated aging tests at 620℃. After 480 hours of aging, the denitrification efficiency of the sample decreased from the initial 96.2% to 95.0%. Based on thermal deactivation principles, this is equivalent to approximately 5.5 years of continuous operation under standard conditions at 350℃. Furthermore, the activity decay rate was tested to be only 0.5% / month, indicating that the catalyst possesses excellent long-term operational stability.
[0038] The catalyst exhibits excellent low-drag characteristics: tests have shown that, under surface velocities of 5–20 m / h, the single-layer flue gas drag of this catalyst is less than 70 Pa.
[0039] Example 2 Preparation of High-Adhesion, Wear-Resistant Composite Modified Flat-Plate Denitration Catalyst A high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst is made from the following components in parts by weight: 70 parts titanium dioxide, 10 parts modified attapulgite, 8 parts composite fiber (2 parts each of 4 different fiber specifications), 8 parts plasticizer, 2.4 parts active component, 0.8 parts dispersant, 3 parts binder, 0.6 parts tungsten-based modifier, 0.4 parts rare earth dopant, and 20 parts water.
[0040] The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of 3:1.
[0041] The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:1. The glass fiber is composed of two specifications: specification 1: diameter 2.5μm, length 1-3 mm; specification 2: diameter 2.5μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:1. The carbon fiber is composed of two specifications: specification 1: diameter 2.5μm, length 1-3 mm; specification 2: diameter 2.5μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:1.
[0042] The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:1.
[0043] The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of 7:3 and a particle size of 60 nm.
[0044] The plasticizer is polyethylene glycol.
[0045] The dispersant is a polycarboxylate.
[0046] The bonding agent is a silica sol with a solid content of 45%.
[0047] The tungsten-based modifier is zirconium tungstate.
[0048] The rare earth dopant is terbium oxide (Tb4O7).
[0049] The preparation method of the high-adhesion, wear-resistant composite modified flat-plate denitration catalyst includes the following steps: S1: Preparation of modified attapulgite: Take attapulgite ore with a purity of 93wt.%, wash it with water, filter it, dry it, mix it with a modifier, the weight ratio of attapulgite to modifier is 10:0.8, hydrothermally treat it at 300℃ for 2.5 hours, dry it, grind it to 100 mesh, and you will get modified attapulgite. S2: One-time mixing: Add modified attapulgite, plasticizer, dispersant and 50% titanium dioxide (35 parts) into the mixer and dry mix for 8 min; then add water and mix once at 50℃ for 20 min to obtain the preliminary mixture. S3: Secondary mixing: Add the composite fiber and the remaining titanium dioxide to the initial mixing material, heat to 65℃, and carry out secondary mixing for 15 minutes to obtain the secondary mixing material. S4: Three-stage mixing: Add the active components, binder, tungsten modifier and rare earth dopant to the primary mixture, maintain the temperature at 65℃, adjust the pH value to 8 (by adjusting the pH value with lactic acid and ammonia water), and perform three-stage mixing for 10 minutes to obtain catalyst sludge. The plasticity of the catalyst sludge is 0.6 and the moisture content is 26%. S5: Ultrasonic treatment and granulation: The catalyst sludge is placed in a container equipped with ultrasonic transmitters on all sides and ultrasonically treated at a frequency of 500kHz for 10 minutes; then granulation is performed to obtain granular activated sludge. S6: Coating and molding: The active mud material is extruded and coated onto a stainless steel screen plate through a coating roller equipped with an electromagnetic rotary heating device. The temperature of the coating roller is controlled at 140℃ and the coating thickness is 0.6 mm. After coating, the coated plate is placed in a drying oven and dried at 160℃ for 4 min. S7: Cutting, pleating and calcining: Cut the dried coated plate to the preset size, and then pleat it. The pleating angle is 30°, the plate width is 16 mm, and the pitch is 2.2 mm. This increases the specific surface area while reducing the flue gas resistance. Combine the pleated plates into catalyst units, put them into a calcining furnace, heat them to 580°C at a heating rate of 5°C / min, and calcine them for 8 hours. Cool them to room temperature to obtain the high-adhesion, wear-resistant composite modified flat plate denitrification catalyst.
[0050] Tests showed that the catalyst had an adhesion of 2.1 MPa to the stainless steel screen plate, a bending strength of 13.8 MPa, a denitrification efficiency of 97.5%, and a stable denitrification efficiency of over 96% within a temperature range of 280–480℃. It also exhibited strong resistance to poisoning, a service life of up to 6 years, and low flue gas resistance.
[0051] Example 3 Preparation of High-Adhesion, Wear-Resistant Composite Modified Flat-Plate Denitrification Catalyst A high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst is made from the following components in parts by weight: 75 parts titanium dioxide, 15 parts modified attapulgite, 10 parts composite fiber (2.5 parts each of 4 different fiber specifications), 12 parts plasticizer, 3 parts active component, 1.2 parts dispersant, 4 parts binder, 0.8 parts tungsten-based modifier, 0.6 parts rare earth dopant, and 25 parts water.
[0052] The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of 3:1.
[0053] The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:1. The glass fiber is composed of two specifications: specification 1: diameter 3μm, length 1-3 mm; specification 2: diameter 3μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:1. The carbon fiber is composed of two specifications: specification 1: diameter 3μm, length 1-3 mm; specification 2: diameter 3μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:1.
[0054] The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:1.
[0055] The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of 7:3 and a particle size of 100 nm.
[0056] The plasticizer is hydroxypropyl methylcellulose.
[0057] The dispersant is sodium citrate.
[0058] The bonding agent is a silica sol with a solid content of 35%.
[0059] The tungsten-based modifier is niobium tungstate.
[0060] The rare earth dopant is samarium oxide (Sm2O3).
[0061] The preparation method of the high-adhesion, wear-resistant composite modified flat-plate denitration catalyst includes the following steps: S1: Preparation of modified attapulgite: Take attapulgite ore with a purity of 95wt.%, wash it with water, filter it, dry it, mix it with a modifier, the weight ratio of attapulgite to modifier is 10:1, hydrothermally treat it at 350℃ for 3 hours, dry it, grind it to 120 mesh, and you will get modified attapulgite. S2: One-time mixing: Add modified attapulgite, plasticizer, dispersant and 50% titanium dioxide (35 parts) into the mixer and dry mix for 10 min; then add water and mix once at 60℃ for 22 min to obtain the preliminary mixture. S3: Secondary mixing: Add the composite fiber and the remaining titanium dioxide to the initial mixture, heat to 70℃, and carry out secondary mixing for 16 minutes to obtain the secondary mixture. S4: Three-stage mixing: The active components, binder, tungsten modifier and rare earth dopant are added to the primary mixture, the temperature is maintained at 70℃, the pH value is adjusted to 9 (by adjusting the pH value with lactic acid and ammonia water), and three-stage mixing is carried out for 11 minutes to obtain catalyst slurry. The plasticity of the catalyst slurry is 0.7 and the moisture content is 24%. S5: Ultrasonic treatment and granulation: The catalyst sludge is placed in a container equipped with ultrasonic transmitters on all sides and ultrasonically treated at a frequency of 700kHz for 8 minutes; then granulation is performed to obtain granular active sludge. S6: Coating and molding: The active mud material is extruded and coated onto a stainless steel screen plate through a coating roller equipped with an electromagnetic rotary heating device. The temperature of the coating roller is controlled at 160℃ and the coating thickness is 0.7 mm. After coating, the coated plate is placed in a drying oven and dried at 170℃ for 3 min. S7: Cutting, pleating and calcining: Cut the dried coated plate to the preset size, and then pleat it. The pleating angle is 35°, the plate width is 17 mm, and the pitch is 2.8 mm. This increases the specific surface area while reducing the flue gas resistance. Combine the pleated plates into catalyst units, put them into a calcining furnace, heat them to 600°C at a heating rate of 10°C / min, and calcine them for 9 hours. Cool them to room temperature to obtain the high-adhesion, wear-resistant composite modified flat plate denitrification catalyst.
[0062] Tests showed that the catalyst had an adhesion of 2.3 MPa to the stainless steel screen plate, a bending strength of 14.5 MPa, a denitrification efficiency of 98.1%, and a denitrification efficiency that remained stable at over 97% within a temperature range of 280–480℃. It also exhibited strong resistance to poisoning, a service life of up to 6.5 years, and low flue gas resistance.
[0063] Comparative Example 1: Preparation of Conventional Plate-Type Denitration Catalyst Using a conventional formula in the existing technology, it is made from the following components in parts by weight: 60 parts of single anatase titanium dioxide, 5 parts of kaolin, 5 parts of glass fiber, 5 parts of carbon fiber, 5 parts of plasticizer, 1.5 parts of active component, 0.4 parts of tungsten-based modifier, 0.3 parts of rare earth dopant, and 15 parts of water.
[0064] The glass fiber comes in two specifications: Specification 1: 5 μm in diameter and 3–6 mm in length; Specification 2: 5 μm in diameter and 2–4 mm in length; the weight ratio of the two specifications of glass fiber is 1:1.
[0065] The carbon fiber has two specifications: Specification 1: diameter of 6μm and length of 3-5 mm; Specification 2: diameter of 6μm and length of 4-8 mm; The weight ratio of the two specifications of carbon fiber is 1:1.
[0066] The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:1.
[0067] The plasticizer is polyvinyl alcohol.
[0068] The tungsten-based modifier is ammonium paratungstate.
[0069] The rare earth dopant is CeO2.
[0070] The main differences from Examples 1, 2, and 3 are: the titanium dioxide used is a single anatase titanium dioxide, not a composite titanium dioxide; the conventional binder mineral component, ordinary kaolin, is used, not modified palladium; the specifications of the glass fiber and carbon fiber used are different; the tungsten modifier used is the conventional tungsten modifier ammonium paratungstate, not niobium tungstate or zirconium tungstate; the rare earth dopant used is the conventional rare earth dopant CeO2, not samarium oxide Sm2O3 or terbium oxide Tb4O7; and no dispersant or binder was added.
[0071] The preparation method is a conventional process, as follows: the components are directly mixed and then kneaded; the kneaded mixture is directly coated; after coating, it is dried, cut, pleated, and calcined at a constant temperature of 550℃ for 6 hours. After cooling, a conventional flat-plate denitrification catalyst is obtained. The main differences from Examples 1, 2, and 3 are: no step of modifying attapulgite; no dispersant or binder added; no premixing, secondary kneading, or tertiary kneading steps; no ultrasonic treatment (to break up component agglomerates); and the calcination is not gradient calcination.
[0072] Comparative Example 2 The composition is the same as in Example 1, except that a single-component modifier—hydrogenated petroleum resin—is used to modify attapulgite, instead of a compound modifier (composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of 3:1). The preparation method is the same as in Example 1.
[0073] Comparative Example 3 The composition is the same as in Example 1. The preparation method is the same as in Example 1, except that ultrasonic treatment is not performed (in step S5, granulation is performed directly without ultrasonic treatment), and gradient calcination is not performed (in step S7, constant temperature calcination is used, directly heating to 550℃ and holding for 6 hours). Without ultrasonic treatment, the agglomerates in the mud cannot be broken up; without gradient calcination, the catalyst layer is prone to cracking.
[0074] Experiment 1 Performance Evaluation The catalysts prepared in Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 were used as samples to test their performance indicators. The test results are shown in Table 1.
[0075] Table 1
[0076] As shown in Table 1, the catalysts prepared in Examples 1, 2, and 3 exhibit excellent performance, significantly outperforming Comparative Examples 1, 2, and 3 in terms of adhesion, mechanical strength, catalytic activity, and service life. They demonstrate significant advantages and outstanding technological innovation and application value. The superior performance of the catalysts of this invention does not depend on any single technique, but rather on the synergistic effect of various techniques (modified attapulgite, compound modifiers, specific tungsten-based modifiers / rare earth dopants, composite titanium dioxide, tertiary mixing, ultrasonic treatment, and gradient calcination).
[0077] The above embodiments are provided to those skilled in the art to fully disclose and describe how the claimed implementations can be carried out and used, and are not intended to limit the scope of the disclosure herein. Modifications that will be obvious to those skilled in the art will be within the scope of the appended claims.
Claims
1. A high-adhesion, wear-resistant composite modified plate-type denitrification catalyst, characterized in that, It is made of the following components in parts by weight: 50-80 parts titanium dioxide, 3-18 parts modified attapulgite, 3-12 parts composite fiber, 2-15 parts plasticizer, 1.2-4 parts active component, 0.3-1.5 parts dispersant, 1-5 parts binder, 0.2-1.0 parts tungsten modifier, 0.1-0.8 parts rare earth dopant, and 10-30 parts water; The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of (2.8-3.2):
1. The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:(0.8-1.2). The glass fiber is composed of two specifications: specification 1: diameter 1.5-3 μm, length 1-3 mm; specification 2: diameter 1.5-3 μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:
1. The carbon fiber is composed of two specifications: specification 1: diameter 1.5-3 μm, length 1-3 mm; specification 2: diameter 1.5-3 μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:
1. The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:(1 to 1.5).
2. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that: The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of (6-8):(2.5-3.5).
3. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that: The plasticizer is selected from any one or more of polyvinyl alcohol, polyethylene glycol, and hydroxypropyl methylcellulose.
4. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that: The dispersant is selected from sodium citrate and / or polycarboxylate.
5. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that: The bonding agent is selected from silica sol with a solid content of 30% to 50%.
6. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that: The tungsten-based modifier is selected from niobium tungstate and / or zirconium tungstate.
7. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that: The rare earth dopant is selected from samarium oxide (Sm2O3) and / or terbium oxide (Tb4O7).
8. The high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to claim 1, characterized in that, It is made from the following components in parts by weight: ①60 parts titanium dioxide, 5 parts modified attapulgite, 5 parts composite fiber, 5 parts plasticizer, 1.5 parts active component, 0.5 parts dispersant, 2 parts binder, 0.4 parts tungsten modifier, 0.3 parts rare earth dopant, and 15 parts water; The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of 3:
1. The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:
1. The glass fiber is composed of two specifications: specification 1: diameter 2μm, length 1-3 mm; specification 2: diameter 2μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:
1. Similarly, the carbon fiber is composed of two specifications: specification 1: diameter 2μm, length 1-3 mm; specification 2: diameter 2μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:
1. The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:
1. The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of 7:3 and a particle size of 80 nm. The plasticizer is polyvinyl alcohol; The dispersant is sodium citrate; The bonding agent is a silica sol with a solid content of 40%; The tungsten-based modifier is niobium tungstate; The rare earth dopant is samarium oxide (Sm2O3); Or ②: 70 parts titanium dioxide, 10 parts modified attapulgite, 8 parts composite fiber, 8 parts plasticizer, 2.4 parts active component, 0.8 parts dispersant, 3 parts binder, 0.6 parts tungsten modifier, 0.4 parts rare earth dopant, and 20 parts water; The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of 3:
1. The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:
1. The glass fiber is composed of two specifications: specification 1: diameter 2.5μm, length 1-3 mm; specification 2: diameter 2.5μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:
1. Similarly, the carbon fiber is composed of two specifications: specification 1: diameter 2.5μm, length 1-3 mm; specification 2: diameter 2.5μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:
1. The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:
1. The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of 7:3 and a particle size of 60 nm. The plasticizer is polyethylene glycol; The dispersant is a polycarboxylate; The bonding agent is a silica sol with a solid content of 45%; The tungsten-based modifier is zirconium tungstate; The rare earth dopant is terbium oxide (Tb4O7); Or ③, 75 parts titanium dioxide, 15 parts modified attapulgite, 10 parts composite fiber, 12 parts plasticizer, 3 parts active component, 1.2 parts dispersant, 4 parts binder, 0.8 parts tungsten modifier, 0.6 parts rare earth dopant, and 25 parts water; The modified attapulgite is obtained by modifying attapulgite with a modifier, which is composed of hydrogenated petroleum resin and polysiloxane, with a weight ratio of hydrogenated petroleum resin to polysiloxane of 3:
1. The composite fiber is a mixture of glass fiber and carbon fiber, with a weight ratio of glass fiber to carbon fiber of 1:
1. The glass fiber is composed of two specifications: specification 1: diameter 3μm, length 1-3 mm; specification 2: diameter 3μm, length 3-6 mm; the weight ratio of the two specifications of glass fiber is 1:
1. Similarly, the carbon fiber is composed of two specifications: specification 1: diameter 3μm, length 1-3 mm; specification 2: diameter 3μm, length 3-6 mm; the weight ratio of the two specifications of carbon fiber is 1:
1. The active component is composed of ammonium heptamolybdate and ammonium metavanadate, with a weight ratio of ammonium heptamolybdate to ammonium metavanadate of 1:
1. The titanium dioxide is a composite titanium dioxide, composed of anatase titanium dioxide and rutile titanium dioxide, with a weight ratio of anatase titanium dioxide to rutile titanium dioxide of 7:3 and a particle size of 100 nm. The plasticizer is hydroxypropyl methylcellulose; The dispersant is sodium citrate; The bonding agent is a silica sol with a solid content of 35%; The tungsten-based modifier is niobium tungstate; The rare earth dopant is samarium oxide (Sm2O3).
9. The preparation method of the high-adhesion, wear-resistant composite modified flat-plate denitration catalyst according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1: Preparation of modified attapulgite: Take attapulgite, mix it with a modifier, the weight ratio of attapulgite to modifier is 10:(0.5~1), hydrothermally treat at 180~420℃ for 1~3.5 hours, dry, grind to 100~120 mesh, and obtain modified attapulgite; S2: One-time mixing: Add modified attapulgite, plasticizer, dispersant and 50% to 70% titanium dioxide to the mixer and dry mix for 2 to 12 minutes; add water and mix once at 25 to 65°C for 8 to 25 minutes to obtain the preliminary mixture. S3: Secondary mixing: Add the composite fiber and the remaining titanium dioxide to the initial mixing material, heat to 45-75℃, and carry out secondary mixing for 8-18 minutes to obtain the secondary mixing material. S4: Three-stage mixing: Add the active components, binder, tungsten modifier and rare earth dopant to the primary mixing material, maintain the temperature at 45-75℃, adjust the pH value to 8-9, and perform three-stage mixing for 5-12 minutes to obtain catalyst slurry. S5: Ultrasonic treatment and granulation: Place the catalyst sludge in a container and ultrasonically treat it at a frequency of 20-800 kHz for 3-25 min; then granulate it to obtain granular activated sludge. S6: Coating and molding: The active mud material is extruded and coated onto a stainless steel screen plate through a coating roller. The temperature of the coating roller is controlled at 80-180℃, and the coating thickness is 0.3-0.8 mm. After coating, the coated plate is dried at 120-180℃ for 3-8 minutes. S7: Cutting, pleating and calcining: Cut the dried coated plate to the preset size, and then pleat it. The pleating angle is 15° to 40°, the plate width is 12 to 18 mm, and the pitch is 2 to 3 mm. Assemble the pleated single plates into catalyst units, put them into a calcining furnace, heat them to 480 to 620°C at a heating rate of 5 to 10°C / min, and calcine them for 3 to 10 hours. Cool them to room temperature to obtain the high-adhesion, wear-resistant composite modified flat plate denitrification catalyst.
10. The application of the high-adhesion, wear-resistant composite modified flat-plate denitrification catalyst according to any one of claims 1 to 8 in selective catalytic reduction flue gas denitrification.
